Stereotip Orang Buleleng Singaraja Bali terhadap Pembentukan Persepsi dalam Membangun Relasi Antarpersonal - Ketut Yuniati (Jurnal Nomosleca, 2023)
Stereotypes are a perspective that refers to both positive and negative things, but a phenomenon that often occurs is that stereotypes are more inclined towards negative values. The aim of the research is to describe the formation of positive interpersonal relationships. The research method is interviews and observation. The results show that the negative stereotype of rude Buleleng people is not proven, the results have warm and friendly communication. The use of harsh words is usually directed at people who are very close. The use of stereotypes prevents someone from seeing the uniqueness of individual beings. Meanwhile, as a group,it eliminates the individual's right to determine themselves as the formation of a society. Likewise with the stereotype of the Beleleng people, if the difference in ways of communicating is perceived as a positive thing, it will forma positive perception which of course will have an impacton positive interpersonal relations.